Risk-Aversion and Social Mobility: The Impossibility of Order-Preserving Income Redistributions - Leif Danziger; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2000)
The traditional criticism notwithstanding, we show that social mobility can, in principle, explain political income redistributions. Nonetheless, the social-mobility argument for redistribution is not satisfactory, as actual transition probabilities are not consistent with order-preserving redistributions.
Keywords: 330; Political economy; social mobility; income redistribution